2009
DOI: 10.1111/j.1460-9568.2009.06869.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage and secretion of β‐NAD, ATP and dopamine in NGF‐differentiated rat pheochromocytoma PC12 cells

Abstract: In nerve-smooth muscle preparations β-nicotinamide adenine dinucleotide (β-NAD) has emerged as a novel extracellular substance with putative neurotransmitter and neuromodulator functions. Thus, β-NAD is released along with noradrenaline and adenosine 5'-triphosphate (ATP) upon firing of action potentials in blood vessels, urinary bladder and large intestine. At present it is unclear whether noradrenaline, ATP and β-NAD are stored in and released from common populations of synaptic vesicles. This matter is unat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 49 publications
(91 reference statements)
0
38
0
1
Order By: Relevance
“…It was found co-stored with acetylcholine in guinea pig cortex, calf superior cervical ganglion, and motor nerve terminals of rat diaphragm [76]; with noradrenaline, it was found in human blood vessels, smooth muscles, and endothelial cells [80]; it was also found in adrenal chromaffin cells together with serotonin, with neuropeptide Y and glutamate in astrocytes, and with dopamine in neuron-differentiated PC12 [81][82][83][84]. Moreover, in other cell types in the nervous tissue, particularly astrocytes, ATP was found also in small synaptic-like vesicles [85].…”
Section: Atp Storagementioning
confidence: 99%
“…It was found co-stored with acetylcholine in guinea pig cortex, calf superior cervical ganglion, and motor nerve terminals of rat diaphragm [76]; with noradrenaline, it was found in human blood vessels, smooth muscles, and endothelial cells [80]; it was also found in adrenal chromaffin cells together with serotonin, with neuropeptide Y and glutamate in astrocytes, and with dopamine in neuron-differentiated PC12 [81][82][83][84]. Moreover, in other cell types in the nervous tissue, particularly astrocytes, ATP was found also in small synaptic-like vesicles [85].…”
Section: Atp Storagementioning
confidence: 99%
“…Asc-403-β-NAD Interestingly, it has recently been suggested that another molecule, β-nicotinamide adenine dinucleotide (β-NAD) like ATP, may also be a co-transmitter and may likely represent a novel extracellular signalling molecule [57,58]. Smyth et al [58] revealed that β-NAD is released from sympathetic nerve terminals and as such suggested that as with ATP, β-NAD has putative neurotransmitter or neuromodulator functions.…”
Section: Asc-421-kn-62mentioning
confidence: 99%
“…Smyth et al [58] revealed that β-NAD is released from sympathetic nerve terminals and as such suggested that as with ATP, β-NAD has putative neurotransmitter or neuromodulator functions. Furthermore, β-NAD has also recently been shown to be a P2Y 1 and P2Y 11 receptor agonist (EC 50 =6.1 at P2Y 1 ) [10,59].…”
Section: Asc-421-kn-62mentioning
confidence: 99%
“…It is suggested that ATP in vesicles is important for acidification of the vesicle lumen, for creating a proton gradient driving vesicular neurotransmitter uptake and for steps of exocytosis itself (15) in addition to serving neurotransmission (5). ATP is present in large dense-cored (LDCV) and small synaptic vesicles (SSV) as well as in chromaffin vesicles (13,27). Loading of ATP occurs through all stages of vesicle formation and recycling and ATP is taken up by vesicles of both reserved and readily releasable pools (6).…”
Section: Storage Of Purines In Synaptic Vesiclesmentioning
confidence: 99%
“…The studies on cellular sources, mechanisms of release, postjunctional targets and functions of extracellular purines in smooth muscle, in particular, are hampered by the complex nature of smooth muscle tissues and the many possible roles of extracellular purines. Nevertheless, continual work has, during the last decade, expanded our view of the role of ATP and other purines (i.e., NAD + and ADPribose, ADPR) in neurotransmission, and this analysis suggests that multiple purines likely contribute to the complex neural regulation of smooth muscle (11,12,13,14), moving the field of purine neurotransmission beyond the sovereign role of ATP.…”
Section: Introductionmentioning
confidence: 99%